Differences in atheroma between Caucasian and Asian subjects with anterior stroke: A vessel wall MRI study. Issue 1 (13th August 2020) - Watase, Hiroko; Shen, Mi; Sui, Binbin; Gao, Peiyi; Zhang, Dong; Sun, Jie; Balu, Niranjan; Hippe, Daniel S; Jarvik, Gail P; Zhao, Xihai; Li, Rui; Chen, Shuo; et al.
Abstract : Background and purpose: While extracranial carotid artery stenosis is more common among Caucasians and intracranial artery stenosis is more common among Asians, the differences in atherosclerotic plaque characteristics have not yet been extensively examined. We sought to investigate plaque location and characteristics within extracranial carotid and intracranial arteries in symptomatic Caucasians and Chinese using vessel wall MRI. Methods: Subjects with recent anterior circulation ischaemic stroke were recruited and imaged at two sites in the USA and China using similar protocols. Both extracranial carotid and intracranial arteries were reviewed to determine plaque location and characteristics. Results: The prevalence of extracranial carotid plaque in Caucasians and Chinese was 73.1% and 49.1%, respectively (p=0.055). Prevalence of intracranial plaque was 38.5% and 69.1% in Caucasians and Chinese, respectively (p=0.02). Furthermore, 42% of Caucasians and 16% of Chinese had high-risk plaque (HRP) features (intraplaque haemorrhage, luminal surface disruption) in the extracranial carotid artery (p=0.03). The prevalence of HRP features in intracranial arteries was not significantly different between the two cohorts (4% vs 11%; p=0.42). Conclusions: Differences in the location and characteristics of cerebrovascular atherosclerosis were identified by vessel wall MRI in US Caucasian and Chinese subjects with recent anterior circulation ischaemic stroke. Extracranial carotid plaques with HRP features were more common in Caucasians. Intracranial plaques were more common in Chinese subjects, but no significant difference between the two cohorts in intracranial HRP prevalence was found. Larger studies using vessel wall imaging to investigate racial differences in cerebrovascular disease may inform underlying mechanisms of HRP development and may ultimately help guide appropriate therapy.